Identifying central tenets needed in our education systems: Results from a pilot integrated clinical apprenticeship. (3rd July 2019) - Simpkin, Arabella L.; McKeown, Andrew; Parekh, Ravi; Kumar, Sonia; Tudor-Williams, Gareth
Abstract: Purpose: The ability of healthcare systems to deliver world-class compassionate care depends on the quality of training and education of staff. Matching student-centered learning with patient-centered care is the focus for much curricula reform. This study explores the effect a novel longitudinal curriculum had on medical students' attitudes and experiences to better identify central tenets needed in our education system. Methods: Single-center, qualitative focus-group study conducted in 2017 of medical students in a longitudinally integrated clinical apprenticeship at a large UK medical school. Students were randomly assigned to focus groups to describe their educational journey and explore how longitudinal learning prepared them for a medical career, valuing their unique position as student participants in the healthcare system. Results: Four themes emerged from students' experiences: navigating the patient journey, their professional development, their learning journey, and the healthcare system. Conclusions: Listening to student voices lends insights for educators refining educational models to produce doctors of tomorrow. This project identified the educational value of students having authentic roles in helping patients navigate the healthcare system and the benefits of consistent mentorship and greater autonomy. The gulf between gaining skills as a future doctor and gaining skills to pass summative exams calls into question assessment methods.